A Decision Support Model for Customer Value Assessment and Supply Quota Allocation - Barbarasoğlu, G; Yazgaç, Ayşe Tülin; AKTİN, AYŞE TÜLİN (TAYLOR & FRANCIS LTD, 11 NEW FETTER LANE, LONDON EC4P 4EE, ENGLAND, 2000)
The aim of this study is to develop a decision support tool for a supplier in a value-chain environment. The supplier under consideration is assumed to provide a strategic product to a number of customers and needs to allocate his capacity among them in a way to maximize his business value. First, an analytic hierarchy process (AHP) structure is designed to represent the criteria which are identified from the supplier's point of view to assess customer performance, and customer priorities are obtained by using the AHP composition principle. Then, these are deployed in numerical algorithms which aim to allocate the total supply capacity among customers as supply quotas. The approach is implemented in an electric motor manufacturer in Turkey, which possesses high competitive power with advanced manufacturing technology.
Keywords: Engineering; Operations Research & Management Science; Manufacturing; Industrial Engineering; mühendislik; Yöneylem Araştırması ve Yönetim Bilimi; Üretim; Endüstri Mühendisliği